Mapping issues and solutions in the management of non-tax state revenue in Indonesia - Amrie Firmansyah; Puji Wibowo (Journal of Law, Administration, and Social Science, 2026)
Non-Tax State Revenue (PNBP) is a significant source of state income that plays a crucial role in supporting state financial management. However, the Financial Audit Agency (BPK) audit report indicates that PNBP management continues to face recurring and systemic problems. This research aims to identify the primary issues of PNBP in Indonesia and to explore alternative solutions discussed in the academic literature through a scoping review. This research combines the findings of the BPK Semester Examination Results Summary (IHPS) for the 2020-2024 period as a basis for problem identification with relevant academic literature as an alternative source of solutions. Literature searches were carried out via Google Scholar using the Publish or Perish application for publications for the 2021-2025 period. Of the 81 articles identified at the initial stage, those with a strong connection and substantive relevance were synthesized in the analysis of research results. The research results identified seven main groups of PNBP problems, namely non-compliance with collection and deposits, weaknesses in determining and applying rates and legal basis, direct use of PNBP, management of receivables and billing, system and data limitations and digitalization, capacity of human resources and management organizations, as well as weak supervision and internal control. A synthesis of the literature reveals that the solutions proposed in previous research often remain partial and fail to fully address the integrated and recurring nature of PNBP problems. This research makes a significant contribution by systematically mapping PNBP problems and solutions based on state audit findings and academic literature, and by highlighting the importance of a comprehensive governance approach to enhancing PNBP management in Indonesia.